Hybrid Governance and Public Value in South African PPPs: Balancing Trust, Accountability and Participation - Mahlatse Ragolane (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
Public–Private Partnerships (PPPs) are increasingly promoted as vehicles for addressing complex service delivery challenges, yet their ability to generate sustainable public value remains contested. This study examines how hybrid governance arrangements in South African PPPs shape public value creation, using Public Value Theory (PVT) and integrating it with a hybrid governance perspective. Using a qualitative research design and secondary data analysis, the study applies a thematic approach guided by the Public Value-Hybrid Governance Interaction Model. The findings reveal that public value creation depends less on the formal adoption of hybrid governance structures than on the quality of their operationalisation across four interlinked dimensions: structural (role clarity and institutional alignment), processual (genuine co-production and stakeholder participation), relational (balance between trust and accountability), and outcome (equitable, legitimate, and sustainable results). This ‘less’ refers to a weaker correlation between the mere existence of hybrid structures and public value, compared to the stronger influence of their operational quality, particularly the extent to which they foster inclusive participation, clear accountability, and trust-building practices. Across these dimensions, persistent legitimacy deficits, institutional ambiguity, compliance-heavy oversight, and tokenistic participation weaken feedback loops essential for sustaining public value. Theoretically, the study extends PVT by positioning the trust-accountability equilibrium as a central determinant of value creation in hybrid contexts, rather than a peripheral moderator. Practically, it recommends governance designs that align institutional logics, embed inclusive participation, calibrate accountability mechanisms, and adopt multidimensional performance measures. By operationalising these principles, PPPs in South Africa can move beyond transactional efficiency towards transformative, equity-driven outcomes.